(3aUd aj GdeXGde GdeTJQcIs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GHf JjejI GdMQGfi GdMeO ddg fMeOg hfSJYjfg aUd ai GdeXGde GdeTJQcI GdJi JWdH ef GdTQcGA eKd GdeTJQcjf ai bQjI Ch eOjfI s
(3BNQgG (B:s
(3hdjYde ef jfUQg hQSdg HGdZjH Cf Gddg bhi YRjR hGddg CYde hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bgd hUMHg hSde hMSHfG Gddg hfYe Gdhcjd JeJ hGdefI ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B16s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs